Local Wisdom Pikukuh Sapuluh Suku Baduy Dalam Konservasi Lingkungan Budaya Desa Kanekes - Halmahera, Mega; Purnama, Anggi Septiya; Hasyim, Fuad; Benardi, Andi Irwan (Geo-Image, 2019)
Baduy tribe is in Kanekes Village, Leuwidamar Subdistrict, Lebak Regency, Banten. The tribe that lives depends on nature and always maintains the balance of nature, through traditional rules and pikukuh sapuluh is the basis of life guidelines and produces Baduy culture both in thinking, acting and behaving. The study, "Local Wisdom Pikukuh Sapuluh Tribe in the Environmental Conservation of Kanekes Village Culture" is intended to find out how the environmental and cultural conservation of the Baduy community towards the environment and future generations (character inheritance), and to find out how the Baduy community maintains a culture with pikukuh traditional rules especially pikukuh sapuluh that applies and preserves the culture of the influences that come outside and to find out land use in Inner Baduy and Outer Baduy related to the use of production forests and the riles that apply to prohibited forests. The research conducted was development research from previous researchers. The type of research used is qualitative research with interviews, observation, field surveys, and documentation using triangulation methods as data analysis techniques.